De la rhétorique au geste : l’actio dans le portrait peint de la Renaissance italienne - Catherine Vermorel (Laboratoire Italien)
As early as the Quattrocento, portraitists such as Marco d’Oggiono and Botticelli depicted gestures described by the De institutione oratoria (Institutes of Oratory). This didactic treatise on rhetoric in twelve volumes, written by Quintilian in the 1st century AD, was also influential in the educational sphere, due to the qualities of the author, an attentive observer of early childhood and a patient pedagogue. In Book XI, Quintilian discusses at length the posture of the orator, his position in space according to his speech, and his gestures, which involve the whole body. His recommendations on a true staging of speech finds a use in preaching, speeches and baroque theatre. This article focuses on the interpretation of this by painters and their patrons during the Renaissance. Although some gestures, advised or disapproved by Quintilian, had become or remained common and did not necessarily require knowledge of this work, others reveal a detailed reading of our author’s works.